Individuation and Evaluation of Translation Quality of Fiction - Bogatyriov, Andrej A. (Respectus Philologicus, 2004)
It is generally admitted that a thorough text translation means constructing adequate substitute for original text structures. The problem of adequacy criteria tends to be treated differently depending on either artistic or non-artistic poetic type of text being translated. In the latter case, close 'Erleben' in depth of text senses is just an arbitrary demand. It tends to be only a matter of producing proper collocations and colligations substitution. Vice versa, in case of translating artistic texts, there arises a problem of individuation techniques helpful to grasp and reproduce global text intention, concerned with artistic illocutive value.